Management of perforating internal inflammatory resorption in the distal root of mandibular first molar with mineral trioxide aggregate - Fernandes, Marina; de Ataide, Ida (Journal of Orofacial Research, 2020)
Internal inflammatory resorption if not detected in the early stages can result in perforation. Once diagnosed, root canal therapy must be initiated immediately, followed by repair of the perforation. This report presents a case of perforating internal inflammatory resorption in the distal root of a mandibular first molar. The canal was thoroughly debrided and calcium hydroxide was placed as an intracanal medicament. After 1 week, the perforation was repaired by complete mineral trioxide aggregate obturation of the distal canal. The biologic properties of MTA aid in sealing the perforation and periapical healing.